Temple and worship in biblical Israel : proceedings of the Oxford Old Testament Seminar - Oxford Old Testament Seminar; Day, John, 1948- (London ; New York : T & T Clark, 2007)
This volume offers up-to-date understanding of the Temple and the various attitudes to it in the Old Testament, Intertestamental literature and the New Testament.
Papers originally delivered to the Oxford Old Testament Seminar between Jan. 2001 and Nov. 2003, subsequently rev. and often expanded.
Includes bibliographical references and index.
Keywords: Temple of Jerusalem (Jerusalem) -- History -- Congresses; Worship in the Bible -- Congresses; Temple of God -- Congresses; Bible -- Criticism, interpretation, etc. -- Congresses; Judaism -- Liturgy -- History -- To 1500 -- Congresses